Greek architects’ social representation of sustainable design - Πάσχου Μαρία (The Greek Review of Social Research, 2014)
The centrality of sustainable design in architectural thought today and the polysemy of its content raise questions regarding its perception by architects. Based on the interpretative pluralism of sustainable design observed in architectural knowledge and practice, the study aims at understanding architects discourses on sustainable design in the light of the theory of social representations. Drawing on the findings of in-depth interviews with Greek architects, the features of the representation of sustainable design - which differentiate sustainable design from what is perceived as unsustainable design - as well as the mechanisms that describe its emergence, unfold.